Consent to discuss participation in research: a pilot study. Issue 2 (26th September 2019) - Walker, Sophie; Potts, Jennifer; Martos, Lola; Barrera, Alvaro; Hancock, Mark; Bell, Stuart; Geddes, John; Cipriani, Andrea; Henshall, Catherine
Abstract : Background: Equitable access to research studies needs to be increased for all patients. There is debate about which is the best approach to use to discuss participation in research in real-world clinical settings. Objective: We aimed to determine the feasibility of asking all clinical staff within one hospital Trust (an organisation that provides secondary health services within the English and Welsh National Health Service) to use a newly created form on the Trust's electronic patient records system, as a means of asking patients to consent to discuss participation in research (the opt-in approach). We also aimed to collect feedback from patients and clinicians about their views of the opt-in approach. Methods: Four pilot sites were selected in the Trust: two memory clinics, an adult mental health team and an acute adult ward. Data were collected in three phases: (1) for 6 months, pilot site staff were asked to complete a consent to discuss participation in research form with patients; (2) staff feedback on the form was collected through an online survey; and (3) patient feedback was collected through focus groups. Findings: Of 1779 patients attending services during the pilot period, 197 (11%) had a form completed by staff and 143 (8%) opted-in to finding out about research. Staff cited limited time, low priority and poor user experience of the electronic patient records system as reasons for low uptake of the form. Patients generally approved of the approach but offered suggestions for improvement. Conclusions: There were mixed results for adopting an opt-in approach; uptake was very low, limiting its value as an effective strategy for improving access to research. Clinical implications: Alternative strategies to the opt-in approach, such as transparent opt out approaches, warrant consideration to maximise access to research within routine clinical care.